INFLAMMATION MARKERS AND ENDOGENOUS INTOXICATION IN PATIENTS WITH ALCOHOLIC LIVER CIRRHOSIS ON THE BACKGROUND OF CHRONIC BRONCHITIS EXACERBATION - Вірстюк, Н. Г.; Кобітович, І. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
The prognosis of the alcoholic liver cirrhosis (ALC) course depends on many factors, one of which is the formation of acute liver failure against the background of chronic liver failure (ACLF) due to immune-inflammatory activation and endotoxemia. Therefore, the early diagnostics of systemic inflammation and endogenous intoxication in patients with ALC against the background of exacerbation of chronic bronchitis (CB) is important. Objective of the research. Study of markers of the systemic immuno-inflammatory and anti-endotoxin response in patients with ALC on the background of exacerbation of CB. Materials and methods of the research. The subject of the study included 123 patients with ALC, class B and C according to Child-Pugh score; 56 cases without combination with CB (group I), 67patients – in combination with CB on the background of exacerbation which lasted more than 2 weeks at the outpatient stage (group II). The control group involved 20 relatively healthy persons of the same age and sex. Blood contents of C-reactive protein (CRP), tumor- necrotising factor alpha (TNF-α) and anti-endotoxin antibodies of classes A, M, G (anti-ET-IgA, anti-ET-IgM and anti-ET-IgG) were determined by the enzyme immunoassay using reagent kits of the French firm “Diameb” and the Netherlands firm “Hycultbiotech”, respectively. Results. It was found that in patients with ALC and ALC in combination with CB, the CRP level was 9.12- and 19.01-fold higher than in the control group; the content of TNF-α was 2.39- and 4.29-fold higher, respectively (p<0.05). In patients with ALC on the background of CB exacerbation there was an increase of the content of anti-endotoxin antibodies: anti-ET-IgA, anti-ET-IgM and anti-ET-IgG were 28.2-, 11.2- and 6.2-fold respectively (p<0.05). The correlations between the TNF-α and CRP, prognostic MELD, CLIF-C ACLF, CLIF-SOFA indeces (r=+0.73; r=+0.46; r=+0.65; r=+0.59 respectively; p<0.05) were determined; also they were determined between indicators of endotoxemia and inflammation: anti-ET-IgM and TNF-α, CRP (r=+0.58; r=+0.61; respectively; p<0.05). Conclusions. The progression of ALC against the background of CB exacerbation is accompanied by manifestations of systemic autoimmune activation and endotoxemia with an increase of blood levels of CRP, TNF-α and anti-endotoxin antibodies: anti-ET-IgA and anti-ET-IgM in the increased content of anti-ET-IgG, that can serve as a therapeutic and prognostic criterion for the progression of the disease and predictor of the ACLF development. Referens Prysyazhnyuk V.P. Age-dependent features of certain pro- and anti-inflammatory cytokines in the blood of patients with nonviral liver cirrhosis. Hastroenterolohiya. 2014; 1(51): 37-43. Rikalo N.A., Romanenko I.V. Modern views upon pathogenesis of acute alcoholic hepatitis and possibility of its treatment. Visnyk Vinnytskoho natsionalnoho medychnoho universytetu. 2014;2.vol.18: 641-645. Tkachenko T.V., Pentiuk L.O., Pentiuk N.O. Bacterial infections in patients with liver cirrhosis. Bukovynskyy medychnyy visnyk. 2015; 3(75).vol.19: 245-253.